PELUANG DAN TANTANGAN MEA: KERJASAMA PENDIDIKAN INDONESIA DI KAWASAN ASEAN - Zainal Abidin (Pascasarjana IAIN Metro, 2016)
The 12th KTT ASEAN (ASEAN Summit) at Cebu emphasized to create MEA 2015 which makes South East Asia as free flow of goods and services zone, investment and skilled labor, and freer flow of capital. As the impact, Indonesia will face the foreign labor invasion as the result of developed country education like as Singapore. In facing this competition, Indonesia government formulate national education strategy with the purpose that the human resources can compete in the world of global business, at least should refer to determinant factors of nation, such as innovation mastery (45%), network mastery (25%), technology mastery (20%), and natural resource wealth mastery (10%). Islamic Collage Publics have opened international class and they have prepared the lecturers who appropriate with international qualification and standard. Islamic Collage Publics also prepare their students with intellectual ability including English and Arabic language mastery and as the result they can compete with ASEAN Countries.